Energy prices and the structure of inflation in European Union countries - Markowski Łukasz; Kotliński Kamil (International Journal of Management and Economics, 2025)
Since 2022, in almost every inflation category, a strong divergence in price dynamics among the EU countries has become visible. The first aim of this paper is to assess the impact of changes in energy prices on the differentiation in price dynamics in individual inflation categories in EU countries. The second aim is to isolate those components of inflation that have significantly differentiated the countries in the crisis year of 2022. The research was conducted based on the vector-autoregressive model, the Granger causality test, cluster analysis and analysis of variance. It can be concluded that there is a causal relationship between energy prices and the differentiation in the price growth rate in certain inflation categories. In 2022, the EU member states were divided into two quite distinct clusters. This article adds value to current research by taking into account the level of variation in the inflation structure among EU countries.